Political Dialectics of Settlements in Railway Border: Critical Analysis of SDG’s Discourse in Surabaya - Geraldy, Galang (Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The phenomenon of settlement spaces on the railway border cannot be exempt from the construction of the Dutch Colonial Government that built the city of Surabaya, focused on economic growth through industrialization and trade. The policy of the Surabaya government provides legality of settlement status and fundamental service rights for local citizens as part of the social sustainability dimension, which then undermines the various relocation efforts that PT KAI (Indonesia railway company) has undertaken. The development of SDGs is expected to transform the reconstruction of residential space to create revitalization in the economic, ecological, and social sustainability dimensions. However, the reality is that Surabaya, which is considered a model of sustainable cities, still needs to implement a concrete space-based political policy based on the SDGs in the settlement space phenomenon. This article roots the phenomenon through the method of critical discourse analysis (CDA), where language, texts, and ideology of sustainability are dominated only by economic and ecological relationships in certain areas and arenas, which are thought to give a positive image and impact on the city. The analysis of the critical discourse is reinforced by Henri Lefebvre's thought in the theory of the production of space (1991) as an analysis in deducting that settlement spaces are not just physical or technical-administrative questions but concern power relations and ideology that encompass social, economic and political life. The SDGs really involve whole elements in reconstructing the political dialectics of space that support the economic, ecological and social dimensions.